18F-FET PET/CT in Early Subventricular Zone Recurrence of Adult Glioblastoma. (June 2021) - Dissaux, Gurvan; Dissaux, Brieg; Bourhis, David; Schick, Ulrike; Querellou, Solène
Abstract : Abstract: Glioma stem cells (GSCs) are the source of tumor recurrence in glioblastoma and are capable of whole tumor regeneration once the treatment has concluded. Compelling evidence from the last decade suggests that GSC may arise from neural stem cells residing in the adult subventricular zone (SVZ). We report the findings of an 18 F-FET PET/CT showing pathological uptake in SVZ with a tumor-background ratio of greater than 1.6, giving evidence for glioblastoma recurrence. This case highlights the particular attention to be paid to the SVZ given the possible development of GSC.